Analisis Pengelolaan Keuangan Terhadap Pemberdayaan Ekonomi Masyarakat (Studi Kasus Remaja Masjid Jami Al-Istiqomah) - Hanggono Arie Prabowo; Lies Sunarmintyastuti; Ary Fiyanto; Indra Setiawan Purba; Hugo Aries Suprapto; Khairunnisa Khairunnisa (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine how financial management is to empower the community's economy at the Jami Al-Istiqomah Mosque. The research method uses a descriptive qualitative approach with data collection techniques in the form of interviews, documentation studies, and field observations. There were three informants in this study, namely the chairman of IRMI, the head of DKM and the community. The results of the study stated that currently the financial management of IRMI (Ikatan Pemuda Istiqomah Mosque) is considered not to have empowered the community's economy because there is no fixed source of funding. The presence of the GISMAS program (Community Infaq Shodaqoh Movement) can help mosque youths to stabilize the existing cash flow. In addition, there is a need for innovation to publish the results of financial reports as well as posting activities and programs for mosque youth, one of which is by creating an official website that can be accessed by all people both inside the mosque and outside the mosque environment, as well as being considered trustworthy in financial management. and transparency is guaranteed so that people believe that the money they give to mosque youth has been used properly.